Penegakan Hukum Tindak Pidana Pemerasan Dengan Ancaman Dalam Pembangunan Properti Di Kota Padang - Kevin Lie; Aria Zurnetti; Elda, Edita (Delicti : Jurnal Hukum Pidana Dan Kriminologi, 2023)
Crime is committed in various forms and developments. One of the things that occurs in society and receives little attention is the crime of extortion and threats. In Padang City there are cases of criminal acts of threats in property development. This was done by thugs under the pretext of security money. This is of course detrimental and requires action by the police. The formulation of the problem in this research is how to enforce the law against the crime of extortion with threats in property development in Padang City and what are the obstacles faced by the police in efforts to enforce the law for the crime of extortion with threats in property development in Padang City. The research method used is empirical legal research supported by field research at the Padang City Police Department by interviewing sources. Based on the results of the research, it shows that law enforcement for the criminal act of extortion with threats in property development carried out by the police is carried out by: 1. Repressive law enforcement through action based on the provisions of the criminal procedure law. 2. Preventive law enforcement, namely by prevention. The various obstacles faced by the Polresta Padang include limited personnel, the public accepting the practice of criminal acts of extortion with threats, criminal acts often occurring in remote areas and minimal reporting from the public